International business in the information and digital age - Tulder, Rob van; Verbeke, Alain; Piscitello, Lucia (Emerald Publishing Limited, 2018)
This volume is dedicated to Lorraine Eden for herlifetime contributions to IB scholarship. Her research, spanning severaldecades, has addressed many interdisciplinary and societal themes at the heartof the IB field. The story of her intellectual journey -- strongly influenced bythe coming of age of the fourth industrial revolution -- is shared in the opening chapterof this volume. This thirteenth volume in the PIBR series covers an increasingly importantarea of research for International Business (IB) scholars: the role ofmultinational enterprises (MNEs) in the digital and information age. A limitednumber of MNEs now dominate the landscape of the digital age, but almost allinternationally operating firms are being affected by prevailing trends. How totake stock of these trends? How to develop resilient international businessmodels? How to regulate? The digital age presents new opportunities but alsomajor challenges for established and emerging MNEs alike. This volume brings together papers from leading IB scholars and from academics in adjacent disciplines such as economic geography,international relations and political science, strategic management, andtechnology studies. Four dimensions of the information and digital age are analyzed using an IB angle: Trends and theories in the information age Entrepreneurial strategies in the informationage; Functional strategies in the information age; Industry 4.0.
Prelims -- Introduction: international business in the information and digital age An overview of themes and challenges -- Chapter 1 The fourth industrial revolution: seven lessons from the past -- Part I Trends and theory in the information age -- Chapter 2 International production and the digital economy -- Chapter 3 IB and strategy research on "new" information and communication technologies: guidance for future research -- Chapter 4 The changing face of international business in the information age -- Chapter 5 The effects of global connectivity on knowledge complexity in the information age -- Part II Entrepreneurial strategies in the information age -- Chapter 6 Blockchain ventures and international business -- Chapter 7 Internationalisation through digitalisation: the impact of e-commerce usage on internationalisation in small- and medium-sized firms -- Chapter 7 Internationalisation through digitalisation: the impact of E-commerce usage on internationalisation in small- and medium-sized firms -- Chapter 9 New digital layers of business relationships experiences from business-to-business social media -- Part III Functional strategies in the information age -- Chapter 10 The changing structure of talent for innovation: on demand online marketplaces -- Chapter 11 Expanding international business via smart services: insights from 'hidden champions' in the machine tool industry -- Chapter 12 Additive manufacturing and global value chains: an empirical investigation at the country level -- Part IV Industry 4.0 -- Chapter 13 Amazon and Alibaba: internet governance, business models, and internationalization strategies -- Chapter 14 Industry 4.0 Technologies and internationalization: insights from Italian companies -- Chapter 15 On the role of clusters in fostering the Industry 4.0 -- Chapter 16 Internationalisation of science parks: experiences of Brazilian innovation environments -- Index.
Includes index.
Print version record
Keywords: International business enterprises -- Technological innovations; International business enterprises -- Data processing; Business & Economics -- International -- General; International business